Monodromy zeta-functions of deformations and Newton diagrams - Gusev, Gleb (Revista Matemática Complutense, 2009)
For a one-parameter deformation of an analytic complex function germ of several variables, there is defined its monodromy zeta-function. We give a Varchenko type formula for this zeta-function if the deformation is non-degenerate with respect to its Newton diagram.